Falling for the Troll: A Children’s Literature Study on Holly Black’s Valiant: A Modern Tale of Faerie (2005) - Alberta Natasia Adji; Athaya Prita Belia (Soegijapranata Catholic University, 2018)
Monsters have always been a part of children fictional tales, representing the evil side of nature. They are the reason why heroes and heroines struggle to fight against, but at the same time they balance the whole realm, existing side by side with the heroes. There have been numerous children stories which depict the monsters as the villains, but they have rarely done so in portraying monsters as the wronged ones. In Holly Black’s Valiant (2005), the troll character named Ravus is presented as an outcast, a banished figure from his folk because of a misjudged rumor in his former kingdom. Unlike others who constantly challenge and trap humans, Ravus becomes a scholar who loves to explore his alchemy. He helps other outlaws to secure their well-being and health, even teaching Valerie the protagonist with her sword practicing, rescuing her whenever possible and eventually falling for her. The study highlights a new perspective on monstrous identity in a young adult book, making a counterpoint in presenting a fact that monsters can also be portrayed as very human and gentle instead of rude and dangerous.